Negative electrode material, negative electrode sheet and manufacturing method thereof, and lithium ion battery and manufacturing method thereof
By using silicon-based materials, carbon covering sinna lines and carbon nanotubes in the negative electrode materials of lithium-ion batteries, a three-dimensional conductive network structure is formed, and the problems of limited specific capacity and poor cycle stability of the negative electrode materials in the prior art are solved, thereby achieving higher battery performance.
Patent Information
- Application Number
- JP2024563389
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2022-05-06
- Publication Date
- 2025-05-02
AI Technical Summary
The specific capacity of the negative electrode materials of existing lithium-ion batteries is limited, and the volume expansion of silicon material during lithium storage leads to poor circulation stability.
The negative electrode material containing silicon-based materials, carbon-covered sinna wires and carbon nanotubes is used to form a three-dimensional conductive network structure to reduce the volume effect caused by lithium insertion and extraction, and improve the specific capacity and cycling stability of the battery.
The specific capacity and cycle stability of lithium-ion batteries are significantly improved, and the ionic and electronic conductivity of the negative electrode material is enhanced.
Smart Images

Figure 2025514214000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to a Chinese patent application bearing application number 2022104462023 and entitled "Negative electrode material, negative electrode sheet, and lithium ion battery" filed on April 26, 2022 with the China Patent Office, and a Chinese patent application bearing application number 2022104462076 and entitled "Negative electrode sheet and battery" filed on April 26, 2022 with the China Patent Office, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the technical field of lithium ion battery materials, and in particular to anode materials, anode sheets, and lithium ion batteries. [Background technology]
[0003] Due to the rapid development and popularity of portable electronic devices and electric vehicles, there is an urgent need for lithium-ion batteries with high specific energy and long cycle life.Currently, commercially available lithium-ion batteries mainly use graphite as the anode material, but the theoretical specific capacity of graphite is only 372mAh / g, which limits the further improvement of the specific energy of lithium-ion batteries.
[0004] Although the theoretical specific capacity of silicon can reach up to 4200mAh / g, the volume of silicon expands by more than 300% during the lithium storage process, which makes the silicon particles easily crushed and the active material falls off the current collector, resulting in a significant reduction in the cycle stability of the electrode. Summary of the Invention [Problem to be solved by the invention]
[0005] In response to at least one of the shortcomings of the prior art, the objectives of the embodiments of the present application include at least providing a negative electrode material, a negative electrode sheet, and a lithium ion battery that can increase the specific capacity of a battery and improve the cycle stability. [Means for solving the problem]
[0006] In a first aspect, embodiments of the present application provide an anode material including a silicon-based material, carbon-coated tin nanowires, and carbon nanotubes.
[0007] Carbon-coated nanowires and carbon nanotubes have a certain length and also have a certain flexibility and elasticity. When mixed with silicon-based materials, they can form a three-dimensional conductive network structure, which can alleviate the volume effect of the negative electrode material caused by lithium intercalation and deintercalation, increase the specific capacity of the battery, improve cycle stability, and the negative electrode material has high ionic conductivity and electronic conductivity and better conductive ability.
[0008] In some embodiments of the present application, the silicon-based material includes at least one of elemental silicon, a silicon alloy, and silicon monoxide.
[0009] In some embodiments of the present application, the silicon element includes at least one of silicon nanoparticles, silicon nanosheets, and silicon nanowires.
[0010] In some embodiments herein, the silicon alloy includes at least one of an aluminum-silicon alloy, a magnesium-silicon alloy, a ferro-silicon alloy, and a silver-silicon alloy.
[0011] In some embodiments of the present application, the silicon nanoparticles have a particle size of 5-200 nm.
[0012] In some embodiments of the present application, the silicon nanosheet has a thickness of 5 to 100 nm and a planar size of 100 to 2000 nm.
[0013] In some embodiments of the present application, the silicon nanowires have a diameter of 5-200 nm and a length of 50-2000 nm.
[0014] In some embodiments of the present application, the surface of the silicon-based material is further coated with a carbon layer of nanoscale thickness.
[0015] In some embodiments of the present application, the carbon layer on the silicon-based material has a thickness of 2-10 nm.
[0016] In some embodiments of the present application, the carbon-coated tin nanowires have a diameter of 100 nm or less and an aspect ratio of 5:1 to 1000:1.
[0017] In some embodiments of the present application, the thickness of the carbon coating layer in the carbon-coated tin nanowires is in the nanoscale.
[0018] In some embodiments of the present application, the carbon coating layer on the carbon-coated tin nanowires has a thickness of 2-10 nm.
[0019] In some embodiments of the present application, the degree of graphitization γ of the carbon coating layer in the carbon-coated tin nanowire satisfies 0.3≦γ≦1, where γ=(0.344−d 002 ) / (0.344-0.3354), where d 002 is the layer spacing in the 002 crystal plane of the carbon coating layer, and is expressed in nm.
[0020] In some embodiments of the present application, the carbon nanotubes have a diameter of 20 nm or less and an aspect ratio of (10-1000):1 (10:1-1000:1).
[0021] In some embodiments herein, the carbon nanotubes include at least single-walled carbon nanotubes.
[0022] In some embodiments herein, the carbon nanotubes are a mixture of single-walled and multi-walled carbon nanotubes.
[0023] In some embodiments of the present application, the negative electrode material has a silicon content of 60% to 98% by weight, a tin content of 0.5% to 20% by weight, and a carbon content of 1.5 to 20% by weight.
[0024] In some embodiments of the present application, the negative electrode material further comprises carbon powder.
[0025] In some embodiments herein, the carbon powder is one or more of graphite, hard carbon, and soft carbon.
[0026] In a second aspect, embodiments of the present application provide a negative electrode sheet comprising the above-described negative electrode material.
[0027] In a third aspect, the present embodiment comprises: mixing the negative electrode material with a solvent, a conductive additive, and a binder to form a negative electrode slurry; and applying the negative electrode slurry onto a negative electrode current collector, drying the slurry, and then forming a negative electrode sheet.
[0028] In a fourth aspect, the present embodiment provides a lithium ion secondary battery including the negative electrode sheet.
[0029] In a fifth aspect, the present embodiment comprises: combining the negative electrode sheet with a positive electrode sheet and a separator to form an electrode assembly; and placing the electrode group in a case and injecting an electrolyte to form a lithium ion secondary battery.
[0030] In a sixth aspect, the present embodiment provides a lithium ion solid state battery including the negative electrode sheet.
[0031] In a seventh aspect, the present embodiment comprises: A method for making a lithium ion solid state battery is provided, comprising combining the negative electrode sheet with a positive electrode sheet and a solid electrolyte to form a lithium ion solid state battery. [Brief description of the drawings]
[0032] In order to more clearly explain the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly described below. However, the following drawings are merely illustrative of some embodiments of the present application, and are not intended to limit the scope. It should be understood that those skilled in the art can obtain other related drawings based on these drawings without making any creative efforts. [Figure 1] FIG. 2 is a structural schematic diagram of a negative electrode material according to an embodiment of the present application. [Diagram 2] FIG. 2 is a scanning electron microscope (SEM) view of a negative electrode material according to Example 1 of the present application. [Diagram 3] FIG. 2 is a transmission electron microscope (TEM) view of a negative electrode material according to Example 1 of the present application. [Figure 4] FIG. 2 is an electrochemical cycle diagram of a half-cell prepared using the negative electrode material according to Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] In the following, in order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the present application are described clearly and completely.
[0034] 1 is a schematic diagram of the structure of an anode material according to an embodiment of the present application, and as shown in FIG 1, the anode material includes a silicon-based material 110, a carbon-coated tin nanowire 120, and a carbon nanotube 130. FIG 1 is a schematic diagram showing the structure of the anode material after these three are mixed together.
[0035] The carbon-coated tin nanowires and carbon nanotubes 130 may have a certain length and a certain flexibility and elasticity, and when they are mixed with the silicon-based material 110, they can form a three-dimensional conductive network structure, which can alleviate the volume effect of the negative electrode material due to lithium intercalation and deintercalation, increase the specific capacity of the battery, improve the cycle stability, and the negative electrode material has high ionic conductivity, electronic conductivity, and better conductive ability.
[0036] The silicon-based material 110 contains silicon and can realize lithium intercalation and deintercalation. The silicon-based material 110 includes, for example, at least one of silicon alone, a silicon alloy, and silicon monoxide. The silicon alloy includes at least one of an aluminum-silicon alloy, a magnesium-silicon alloy, a ferrosilicon alloy, and a silver-silicon alloy.
[0037] The size of the silicon-based material 110 may be nanoscale or micronscale. The silicon-based material 110 may be granular, flake-like, linear, etc. Taking silicon as an example, the silicon as an element includes at least one of silicon nanoparticles, silicon nanosheets, and silicon nanowires.
[0038] Here, the silicon nanoparticles are granular silicon elements having a nanoscale particle size. The particle size of the silicon nanoparticles may be 5 to 200 nm. The particle size of the silicon nanoparticles means the maximum outer diameter of the silicon nanoparticles. For example, the particle size of the silicon nanoparticles may be 5 nm, 10 nm, 20 nm, 40 nm, 80 nm, 120 nm, 160 nm, or 200 nm.
[0039] A silicon nanosheet is a flake-shaped silicon unit having a nanoscale thickness. The silicon nanosheet may have a thickness of 5 to 100 nm and a planar size of 100 to 2000 nm. The thickness of a silicon nanosheet means the maximum distance between two surfaces of the silicon nanosheet, and the planar size of a silicon nanosheet means the maximum distance between two points on the contour line of a projected image of the silicon nanosheet having the flake-like structure on a horizontal plane. For example, the thickness of a silicon nanosheet may be 5 nm, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, or 100 nm, and the planar size of a silicon nanosheet may be 100 nm, 200 nm, 400 nm, 600 nm, 800 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm, or 2000 nm.
[0040] Silicon nanowires are linear silicon molecules with a nanoscale diameter. Silicon nanowires have a diameter of 5 to 200 nm and a length of 50 to 2000 nm. The diameter of a silicon nanowire is the diameter of the portion having the maximum diameter among various regions of the silicon nanowire. For example, the silicon nanowire may have a diameter of 5 nm, 10 nm, 20 nm, 40 nm, 80 nm, 120 nm, 160 nm, or 200 nm, and a length of 50 nm, 100 nm, 200 nm, 400 nm, 600 nm, 800 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm, or 2000 nm.
[0041] The surface of the silicon-based material 110 may be further coated with a carbon layer having a nanoscale thickness. Since the carbon layer is thin, the specific capacity of the negative electrode material can be kept high. In addition, the carbon layer coating can provide a material with excellent conductivity to the surface of the silicon-based material 110, and when the coated silicon-based material 110 is combined with the carbon-coated tin nanowires 120 and the carbon nanotubes 130, a negative electrode material with a better conductive network can be formed, improving the conductivity of the entire negative electrode material. In addition, the carbon layer can suppress direct contact between the silicon-based material 110 and the electrolyte to a certain extent, and can further improve the cycle stability of the negative electrode material. The thickness of the carbon coating layer on the silicon-based material 110 may be 2 to 10 nm.
[0042] The carbon-coated tin nanowires 120 are tin nanowires coated with a carbon coating layer on the surface. The carbon-coated tin nanowires 120 thus formed also have a linear structure, but their size is nanoscale. The tin material itself has excellent electrical conductivity and high ionic conductivity, so that when combined with the carbon coating layer, the carbon-coated tin nanowires 120 having rapid charging and discharging capabilities can be formed. In addition, the carbon layer coating ensures the structural integrity of the carbon-coated tin nanowires 120 during the charging and discharging process, and achieves excellent electrical contact. The thickness of the carbon coating layer of the carbon-coated tin nanowires 120 may be nanoscale. The thickness of the carbon coating layer of the carbon-coated tin nanowires 120 may be 2 to 10 nm.
[0043] The carbon-coated tin nanowires 120 may have a diameter of 100 nm or less and an aspect ratio of (5-1000):1. The diameters of different parts of the carbon-coated tin nanowires 120 may be the same or different. When the diameter is 100 nm or less and the aspect ratio is (5-1000):1, the flexibility of the carbon-coated tin nanowires 120 can be improved, and when mixed with other materials, a better three-dimensional conductive network structure can be formed. The aspect ratio of the carbon-coated tin nanowires 120 may be 5:1, 10:1, 20:1, 40:1, 80:1, 160:1, 320:1, 480:1, 600:1, or 1000:1.
[0044] The degree of graphitization γ of the carbon coating layer in the carbon-coated tin nanowires 120 satisfies 0.3≦γ≦1, where γ=(0.344−d 002 ) / (0.344-0.3354), where d 002 is the layer spacing in the 002 crystal plane of the carbon coating layer, and is expressed in nm.
[0045] The carbon coating layer of the carbon-coated tin nanowires 120 may have a degree of graphitization γ in the range of 0.3 to 1, which provides a high degree of graphitization and thus allows the negative electrode material to have high efficiency and cycle characteristics.
[0046] Carbon nanotubes 130 are tubular carbon materials with an outer diameter on the nanoscale. Carbon nanotubes 130 have a diameter of 20 nm or less and an aspect ratio of (10-1000):1. Different parts of carbon nanotubes 130 may have the same or different diameters. A diameter of 20 nm or less and an aspect ratio of (10-1000):1 can improve the flexibility of carbon nanotubes 130, and can form a better three-dimensional conductive network when mixed with other materials.
[0047] The carbon nanotubes 130 include at least single-walled carbon nanotubes 130, which can improve the performance of the negative electrode material. The carbon nanotubes 130 may also be a mixture of single-walled carbon nanotubes 130 and multi-walled carbon nanotubes 130.
[0048] In the negative electrode material according to the embodiment of the present application, the silicon content is 60% to 98% by weight, the tin content is 0.5% to 20% by weight, and the carbon content is 1.5 to 20% by weight. Here, the silicon, tin, and carbon contents (wt%) refer to the contents of each element, for example, the carbon content (wt%) refers to the total content (wt%) of carbon in the carbon-coated tin nanowires 120 and carbon in the carbon nanotubes 130 in the negative electrode material, the silicon content (wt%) refers to the silicon content (wt%) in the silicon-based material 110 in the negative electrode material, and the tin content (wt%) refers to the tin content (wt%) in the carbon-coated tin nanowires 120 in the negative electrode material.
[0049] For example, the silicon content may be 60%, 65%, 70%, 74%, 78%, 82%, 86%, 90%, 94%, or 98% by weight, the tin content may be 0.5%, 1%, 2%, 4%, 8%, 12%, 16%, or 20% by weight, and the carbon content may be 1.5%, 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, or 20% by weight.
[0050] The negative electrode material is a silicon-based negative electrode material, and may be mixed with a carbon-based negative electrode material. The negative electrode material may further include carbon powder. For example, the carbon powder may be one or more of graphite, hard carbon, and soft carbon.
[0051] The embodiment of the present application further provides a negative electrode sheet comprising the above-mentioned negative electrode material, which includes all the technical features of the above-mentioned negative electrode material and can achieve the same beneficial technical effects as the above-mentioned negative electrode material, and the specifics are as described above in the description of the negative electrode material, so that the description thereof is omitted.
[0052] An embodiment of the present application further provides a method for manufacturing the negative electrode sheet, the method including: mixing the negative electrode material with a solvent, a conductive additive, and a binder to form a negative electrode slurry; and coating the negative electrode slurry on a negative electrode current collector and drying it to form a negative electrode sheet.
[0053] The present embodiment further provides a lithium ion secondary battery comprising the negative electrode sheet, which includes all the technical features of the negative electrode sheet and can achieve the same beneficial technical effects as the negative electrode material and the negative electrode sheet, and the specifics are as described above in the description of the negative electrode material, so that the description is omitted.
[0054] An embodiment of the present application provides a method for manufacturing the lithium ion secondary battery, the method including the steps of combining a negative electrode sheet with a positive electrode sheet and a separator to form an electrode group, and placing the electrode group in a case and injecting an electrolyte to form a lithium ion secondary battery.
[0055] The present embodiment further provides a lithium ion solid state battery comprising the above-mentioned negative electrode sheet, which includes all the technical features of the above-mentioned negative electrode sheet, and can achieve the same beneficial technical effects as the above-mentioned negative electrode material and the above-mentioned negative electrode sheet, and the specifics are as described above in the description of the negative electrode material, so that the description is omitted.
[0056] The present embodiment further provides a method for manufacturing the above lithium ion solid state battery, which comprises combining the negative electrode sheet with a positive electrode sheet and a solid electrolyte to form a lithium ion solid state battery.
[0057] In order to clarify the purpose, technical solutions and advantages of the embodiments of the present application, the technical solutions in the embodiments of the present application are described below clearly and completely. If no specific conditions are described in the embodiments, the conventional conditions or the conditions recommended by the manufacturers are followed. In addition, the reagents and equipment used without the manufacturer's name are all ordinary products available on the market. Example 1
[0058] (1) Preparation of carbon nanotube solution The carbon nanotubes were dispersed in an ethanol solvent such that the mass ratio of the carbon nanotubes to the ethanol was 1:100, to obtain a carbon nanotube solution. (2) Manufacturing of anode materials Silicon powder with a particle size of 5-10 μm and polyvinylpyrrolidone (PVP) were added to the carbon nanotube solution in step (1), which was homogenized and dispersed using a homogenizer. The homogenized and dispersed suspension was polished in a sand mill. After polishing was completed, tin nanowires and PVP were added and dispersed in the homogenizer. The mixture was then filtered, washed, and baked to obtain a uniformly dispersed composite precursor. Finally, the composite precursor was placed in a high-temperature sintering furnace and sintered in a mixed atmosphere of nitrogen and acetylene by increasing the temperature from room temperature to 700°C. When sintering was completed, the negative electrode material was obtained. (3) Manufacturing of negative electrode sheets The negative electrode material from step (2), conductive agent SP, and sodium alginate were added to water in a ratio of 80:5:15 and stirred continuously to obtain a negative electrode slurry. The negative electrode slurry was applied to the surface of copper foil with a spatula, and baked and dried to obtain a negative electrode sheet. The negative electrode sheet was subjected to a cold press process, and a disk with a diameter of 15 mm was produced from the cold pressed negative electrode sheet using a hole punch. (4) Manufacturing of half cells The negative electrode sheet from step (3) and the lithium sheet were combined to assemble a button half-cell in a glove box filled with argon gas. Here, a Celgard 2300 membrane was used as the separator, and the electrolyte was a 1 mol / L solution of LiPF6 dissolved in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC) in a volume ratio of 4.8:4.8:0.4. Measurements showed that the negative electrode material obtained in step (2) of Example 1 included silicon nanoparticles, carbon-coated tin nanowires, and carbon nanotubes. A carbon coating layer was formed on the surface of the silicon nanoparticles. The silicon nanoparticles had a particle diameter of 50-200 nm. The carbon-coated tin nanowires had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotubes had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 82.4 wt% of the negative electrode material, tin accounted for 5.6 wt% of the negative electrode material, carbon accounted for 9.9 wt% of the negative electrode material, and other substances accounted for 2.1 wt% of the negative electrode material. Example 2
[0059] In Example 2, the remaining steps were the same as in Example 1, except that the silicon powder having a particle size of 5-10 μm was replaced with silicon monoxide having a particle size of 5-10 μm. Measurements showed that the negative electrode material of Example 2 contained a silicon-based material, a carbon-coated tin nanowire, and a carbon nanotube. The silicon-based material was a silicon monoxide nanosheet and silicon monoxide nanoparticles, and a carbon layer was formed on the surface of the silicon monoxide nanosheet and the silicon monoxide nanoparticles. The silicon monoxide nanosheet had a thickness of 20 to 800 nm and a planar size of 200 to 500 nm. The silicon monoxide nanoparticles had a particle size of 50 to 200 nm. The carbon-coated tin nanowire had a diameter of 20 to 80 nm and an aspect ratio of (50 to 500):1. The carbon nanotubes had a diameter of 10 to 20 nm and an aspect ratio of (100 to 200):1. In terms of weight percentage, silicon accounts for 63.5 wt% of the negative electrode material, oxygen accounts for 30.5 wt% of the negative electrode material, tin accounts for 3.4 wt% of the negative electrode material, carbon accounts for 5.2 wt% of the negative electrode material, and other materials account for 2.6 wt% of the negative electrode material. Example 3
[0060] In Example 3, compared to Example 1, the silicon powder having a particle size of 5 to 10 μm in Example 1 was changed to a ferrosilicon alloy having a particle size of 5 to 10 μm, and the remaining steps were the same as those in Example 1. According to the measurement, the negative electrode material of Example 3 includes a silicon-based material, a carbon-coated partial tin nanowire, and a carbon nanotube. The silicon-based material is a ferrosilicon alloy nanosheet and a ferrosilicon alloy nanoparticle, and a carbon layer is formed on a part of the surface of the ferrosilicon alloy nanosheet and the ferrosilicon alloy nanoparticle. The ferrosilicon alloy nanosheet has a thickness of 20 to 100 nm and a planar size of 100 to 600 nm. The particle diameter of the ferrosilicon alloy nanoparticle is 5 to 200 nm. The carbon-coated tin nanowire has a diameter of 20 to 80 nm and an aspect ratio of (50 to 500):1. The carbon nanotube has a diameter of 10 to 20 nm and an aspect ratio of (100 to 200):1. In terms of weight percentage, silicon accounts for 76.6 wt% of the negative electrode material, silicon accounts for 12.8 wt% of the negative electrode material, tin accounts for 4.3 wt% of the negative electrode material, carbon accounts for 5.5 wt% of the negative electrode material, and other materials account for 0.8 wt% of the negative electrode material. Example 4
[0061] In Example 4, compared to Example 1, the silicon powder having a particle size of 5 to 10 μm was replaced with cutting waste of solar silicon wafers, and the remaining steps were the same as those of Example 1. Measurements showed that the negative electrode material of Example 4 included silicon nanosheets, silicon nanoparticles, carbon-coated tin nanowires, and carbon nanotubes. A carbon layer was formed on the surface of the silicon nanosheets. The silicon nanosheets had a thickness of 10-80 nm and a planar size of 200-800 nm. The silicon nanoparticles had a particle diameter of 5-200 nm. The carbon-coated tin nanowires had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotubes had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 85.6 wt% of the negative electrode material, tin accounted for 4.8 wt% of the negative electrode material, carbon accounted for 5.9 wt% of the negative electrode material, and other substances accounted for 3.7 wt% of the negative electrode material. Example 5
[0062] (1) Preparation of carbon nanotube solution The carbon nanotubes were dispersed in an ethanol solvent such that the mass ratio of the carbon nanotubes to ethanol was 1:100, to obtain a carbon nanotube solution. (2) Manufacturing of active materials The carbon nanotube solution was mixed with cutting waste of solar silicon wafers, tin oxide, and polyvinylpyrrolidone (PVP), homogenized and dispersed in a homogenizer, and the homogenized and dispersed suspension was polished in a sand mill for 5 hours, then filtered, washed, and baked to obtain a uniformly dispersed composite precursor. Finally, the composite precursor was placed in a high-temperature sintering furnace and sintered in a nitrogen atmosphere by raising the temperature from room temperature to 700°C, and acetylene gas was introduced to perform carbon coating. When sintering was completed, the active material was obtained. (3) Manufacturing of negative electrode sheets The active material from step (2), conductive agent SP, and sodium alginate were added to water in a ratio of 80:5:15 and stirred to obtain a negative electrode slurry. The negative electrode slurry was applied to the surface of copper foil with a spatula, and baked and dried to obtain a negative electrode sheet. The negative electrode sheet was subjected to a cold press process, and a disk with a diameter of 15 mm was produced from the cold pressed negative electrode sheet using a hole punch. (4) Manufacturing of half cells The negative electrode sheet from step (3) and the lithium sheet were combined to assemble a button half-cell in a glove box filled with argon gas. A Celgard 2300 membrane was used as the separator, and the electrolyte was a 1 mol / L solution of LiPF6 dissolved in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC) in a volume ratio of 4.8:4.8:0.4. Measurements showed that the active material of Example 5 included a silicon nanosheet, a carbon-coated tin nanowire, and a carbon nanotube, and the surface of the silicon nanosheet was coated with a carbon layer. The silicon nanosheet had a thickness of 10-80 nm and a planar size of 200-800 nm. The carbon-coated tin nanowire had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotube had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 85.3 wt% of the active material, tin accounted for 4.2 wt% of the active material, carbon accounted for 8.3 wt% of the active material, and the remaining materials accounted for 2.2 wt% of the active material. Example 6
[0063] (1) Production of active materials Cutting waste of solar silicon wafers, tin oxide, polyvinylpyrrolidone (PVP), ammonium molybdate, and magnesium nitrate were homogenized and dispersed in a homogenizer, and the homogenized and dispersed suspension was polished in a sand mill for 5 hours, then filtered, washed, and baked to obtain a uniformly dispersed composite precursor. Finally, the composite precursor was placed in a high-temperature sintering furnace and sintered in a nitrogen atmosphere by raising the temperature from room temperature to 700°C, and acetylene gas was introduced to perform carbon coating. When sintering was completed, the active material was obtained. (2) Manufacturing of negative electrode sheets The active material from step (1), conductive agent SP, and sodium alginate were added to water in a ratio of 80:5:15 and stirred to obtain a negative electrode slurry. The negative electrode slurry was applied to the surface of copper foil with a spatula, and baked and dried to obtain a negative electrode sheet. The negative electrode sheet was subjected to a cold press process, and a disk with a diameter of 15 mm was produced from the cold pressed negative electrode sheet using a hole punch. (3) Manufacturing of half cells The negative electrode sheet from step (2) and the lithium sheet were combined to assemble a button half-cell in a glove box filled with argon gas. A Celgard 2300 membrane was used as the separator, and the electrolyte was a 1 mol / L solution of LiPF6 dissolved in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC) in a volume ratio of 4.8:4.8:0.4. Measurements showed that the active material of Example 6 contained a silicon nanosheet, a carbon-coated tin nanowire, and a carbon nanotube, and the surface of the silicon nanosheet was coated with a carbon layer. The silicon nanosheet had a thickness of 10-80 nm and a planar size of 200-800 nm. The carbon-coated tin nanowire had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotube had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 85.5 wt% of the active material, tin accounted for 4.9 wt% of the active material, carbon accounted for 5.5 wt% of the active material, and the remaining materials accounted for 4.1 wt% of the active material. Example 7
[0064] (1) Preparation of carbon nanotube solution The carbon nanotubes and the carbon-coated tin nanowires were dispersed in an ethanol solvent so that the mass ratio of the carbon nanotubes to ethanol was 1:100, to obtain a carbon nanotube solution. (2) Manufacturing of anode materials Silicon powder with a particle size of 50 to 120 nm and polyvinylpyrrolidone (PVP) were added to the solution in which the carbon nanotubes and carbon-coated tin nanowires were dispersed in step (1), and the mixture was homogenized and dispersed in a homogenizer. The mixture was then filtered, washed, and baked to obtain a uniformly dispersed composite precursor. Finally, the composite precursor was placed in a high-temperature sintering furnace and sintered in a mixed atmosphere of nitrogen and acetylene by increasing the temperature from room temperature to 700°C. When sintering was completed, the negative electrode material was obtained. (3) Manufacturing of negative electrode sheets The negative electrode material from step (2), conductive agent SP, and sodium alginate were added to water in a ratio of 80:5:15 and stirred continuously to obtain a negative electrode slurry. The negative electrode slurry was applied to the surface of copper foil with a spatula, and baked and dried to obtain a negative electrode sheet. The negative electrode sheet was subjected to a cold press process, and a disk with a diameter of 15 mm was produced from the cold pressed negative electrode sheet using a hole punch. (4) Manufacturing of half cells The negative electrode sheet from step (3) and the lithium sheet were combined to assemble a button half-cell in a glove box filled with argon gas. A Celgard 2300 membrane was used as the separator, and the electrolyte was a 1 mol / L solution of LiPF6 dissolved in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC) in a volume ratio of 4.8:4.8:0.4. Measurements showed that the negative electrode material of Example 7 contained silicon nanoparticles, carbon-coated tin nanowires, and carbon nanotubes, and the surfaces of the silicon nanoparticles were coated with a carbon layer. The silicon nanoparticles had a diameter of 50-120 nm. The carbon-coated tin nanowires had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotubes had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 84.3 wt% of the negative electrode material, tin accounted for 4.9 wt% of the negative electrode material, carbon accounted for 6.3 wt% of the negative electrode material, and the remaining materials accounted for 4.5 wt% of the negative electrode material. Example 8
[0065] In Example 8, compared to Example 1, silicon powder having a particle size of 5 to 10 μm was changed to a silicon nanosheet having a thickness of 10 to 50 nm and a planar size of 100 to 600 nm, and the remaining steps were the same as in Example 1. Measurements showed that the negative electrode material of Example 8 contained silicon nanosheets, carbon-coated tin nanowires, and carbon nanotubes. The silicon nanosheets had a thickness of 10-50 nm and a planar size of 100-600 nm. The carbon-coated tin nanowires had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotubes had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 83.8 wt% of the negative electrode material, tin accounted for 5.1 wt% of the negative electrode material, carbon accounted for 6.2 wt% of the negative electrode material, and other substances accounted for 4.9 wt% of the negative electrode material. Example 9
[0066] In Example 9, compared to Example 1, silicon powder having a particle size of 5 to 10 μm was changed to silicon nanowires having a diameter of 5 to 200 nm and a length of 50 to 2000 nm, and the remaining steps were the same as those of Example 1. Measurements showed that the negative electrode material of Example 8 included silicon nanowires, carbon-coated tin nanowires, and carbon nanotubes. The silicon nanowires had a diameter of 5-200 nm and a length of 50-2000 nm. The carbon-coated tin nanowires had a diameter of 20-80 nm and an aspect ratio of (50-500):1. The carbon nanotubes had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 82.2 wt% of the negative electrode material, tin accounted for 5.6 wt% of the negative electrode material, carbon accounted for 6.9 wt% of the negative electrode material, and other substances accounted for 5.3 wt% of the negative electrode material. Comparative Example 1
[0067] In Comparative Example 1, compared to Example 1, carbon nanotubes and tin nanowires were not added, and the remaining steps were the same as those of Example 1. Measurements showed that the negative electrode material obtained in Comparative Example 1 contained only silicon nanoparticles, and a carbon layer was formed on the surface of the silicon nanoparticles. The particle diameter of the silicon nanoparticles was 50 to 200 nm. In terms of weight percentage, silicon accounted for 95.3 wt% of the negative electrode material, carbon accounted for 3.8 wt% of the negative electrode material, and other substances accounted for 0.9 wt% of the negative electrode material. Comparative Example 2
[0068] In Comparative Example 2, compared to Example 1, no tin nanowires were added, and the remaining steps were the same as those of Example 1. Measurements showed that the negative electrode material obtained in Comparative Example 2 contained silicon nanoparticles and carbon nanotubes, with a carbon layer formed on the surface of the silicon nanoparticles. The silicon nanoparticles had a particle size of 50-200 nm. The carbon nanotubes had a diameter of 10-20 nm and an aspect ratio of (100-200):1. In terms of weight percentage, silicon accounted for 92.2 wt% of the negative electrode material, carbon accounted for 6.7 wt% of the negative electrode material, and other substances accounted for 1.1 wt% of the negative electrode material. Comparative Example 3
[0069] In Comparative Example 3, compared to Example 1, no carbon nanotubes were added, and the remaining steps were the same as those of Example 1. Measurements showed that the negative electrode material obtained in Comparative Example 3 contained silicon nanoparticles and carbon-coated tin nanowires, with a carbon layer formed on the surface of the silicon nanoparticles. The silicon nanoparticles had a particle size of 50-200 nm, and the carbon-coated tin nanowires had a diameter of 20-80 nm and an aspect ratio of (50-500):1. In terms of weight percentage, silicon accounted for 89.2 wt% of the negative electrode material, tin accounted for 4.3 wt% of the negative electrode material, carbon accounted for 5.7 wt% of the negative electrode material, and other substances accounted for 0.8 wt% of the negative electrode material. Comparative Example 4
[0070] In Comparative Example 5, compared to Example 1, in step (2), cutting waste of solar silicon wafers and polyvinylpyrrolidone (PVP) were added to the carbon nanotube solution in step (1), which was homogenized and dispersed in a homogenizer, then filtered, washed, and baked to obtain a uniformly dispersed composite precursor. Finally, the composite precursor was placed in a high-temperature sintering furnace, and sintered by raising the temperature from room temperature to 700°C in a mixed atmosphere of nitrogen and acetylene. When sintering was completed, the composite precursor was dispersed in an ethanol solvent to obtain a dispersant, and tin nanowires were further added, which were homogenized and dispersed in a homogenizer, then filtered, washed, and baked to obtain a negative electrode material. The remaining steps were the same as in Example 1. Measurements showed that the negative electrode material of Comparative Example 5 contained a silicon-based material, tin nanowires, and carbon nanotubes. The silicon-based material contained amorphous silicon particles with a particle diameter of 1 to 10 μm, and a carbon layer was formed on the surface of the silicon particles. The tin nanowires had a diameter of 20 to 80 nm and an aspect ratio of (50 to 500):1. The carbon nanotubes had a diameter of 10 to 20 nm and an aspect ratio of (100 to 200):1. In terms of weight percentage, silicon accounted for 87.8 wt% of the negative electrode material, tin accounted for 4.1 wt% of the negative electrode material, carbon accounted for 4.8 wt% of the negative electrode material, and other substances accounted for 3.3 wt% of the negative electrode material. Comparative Example 5
[0071] In Comparative Example 5, compared with Example 1, in step (2), silicon powder having a particle size of 5 to 10 μm and polyvinylpyrrolidone (PVP) were added to the carbon nanotube solution in step (1), homogenized and dispersed in a homogenizer, then filtered, washed, and baked to obtain a uniformly dispersed composite precursor. Finally, the composite precursor was placed in a high-temperature sintering furnace and sintered in a mixed atmosphere of nitrogen and acetylene by raising the temperature from room temperature to 700° C. After sintering was completed, the composite precursor was dispersed in an ethanol solvent to obtain a dispersant, and tin nanowires were further added and homogenized and dispersed in a homogenizer, followed by filtering, washing, and baking to obtain a negative electrode material. The remaining steps were the same as those in Example 1. When measured, the negative electrode material of Comparative Example 5 contains a mixture of silicon-based material, tin nanowires, and carbon nanotubes. The silicon-based material contains silicon particles with a particle diameter of 5 to 10 μm, and a carbon layer is formed on the surface of the silicon particles. The tin nanowires have a diameter of 20 to 80 nm and an aspect ratio of (50 to 500): 1. The carbon nanotubes have a diameter of 10 to 20 nm and an aspect ratio of (100 to 200): 1. In terms of weight percentage, silicon accounts for 89.3 wt% of the negative electrode material, tin accounts for 4.1 wt% of the negative electrode material, carbon accounts for 4.2 wt% of the negative electrode material, and other substances account for 2.4 wt% of the negative electrode material. Test results and analysis
[0072] (1) Initial characteristics and cycle stability Using an indigo charge / discharge test device, constant current charging and discharging of the half-cell was performed under conditions of a cutoff voltage of 0.005 to 1.0 V and a charge / discharge rate of 0.2 C, and the charge capacity at the first cycle, the coulombic efficiency at the first cycle, the charge capacity at the 100th cycle, and the coulombic efficiency at the 100th cycle were tested. The cycle capacity retention rate at the 100th cycle was calculated using the following formula. Cycle capacity retention rate at the 100th cycle = charge capacity at the 100th cycle / charge capacity at the 1st cycle × 100%. Table 1 shows data on the specific charge capacity at the 1st cycle, the coulombic efficiency at the 1st cycle, the coulombic efficiency at the 100th cycle, and the cycle capacity retention rate at the 100th cycle for each of the Examples and Comparative Examples.
[0073] [Table 1] Initial characteristics and cycle stability of half-cell JPEG2025514214000002.jpg148169
[0074] Referring to the Examples and Table 1, all half-cells manufactured using the negative electrode materials according to the Examples of the present application had a first cycle charge capacity of more than 2500 mAh / g, a first cycle Coulombic efficiency of more than 87%, and a cycle capacity retention rate of more than 78% at the 100th cycle, showing excellent overall performance, whereas half-cells manufactured using the negative electrode materials according to the Comparative Examples generally showed poor cycle stability. (2) Rate characteristics
[0075] Using an invertor charge / discharge tester, constant current charging and discharging of the half-cell was performed with the cutoff voltage set at 0.005 to 1.0 V, and tests were performed at rates of 0.1 C, 0.2 C, 0.5 C, 1 C, and 0.2 C. The capacity retention rate at various rates was calculated using the following formula. Capacity retention rate at a certain rate = charging capacity at that rate / charging capacity at 0.1C rate × 100%. Table 2 shows capacity retention data at various rates for each of the examples and comparative examples.
[0076] [Table 2] Half-cell rate characteristics JPEG2025514214000003.jpg154165
[0077] With reference to the Examples and Table 2, it was found that the half-cells manufactured using the negative electrode materials according to the Examples of the present application basically had a capacity retention rate of more than 60% at a 1C rate, while the half-cells manufactured using the negative electrode materials according to the Comparative Examples basically had a capacity retention rate of less than 30% at a 1C rate.
[0078] FIG. 2 is a scanning electron microscope (SEM) image of the negative electrode material according to Example 1 of the present application, and FIG. 3 is a transmission electron microscope (TEM) image of the negative electrode material according to Example 1 of the present application. From FIG. 2 and FIG. 3, it can be seen that the carbon-coated tin nanowires and carbon nanotubes are distributed on the surface of and between the flaky silicon and the granular silicon. The inventors have speculated that since the carbon-coated tin nanowires and carbon nanotubes have a certain length and also have excellent flexibility and elasticity, the structure of the carbon-coated tin nanowires is completely maintained during the charge and discharge process, and the active materials in the negative electrode material can be brought into contact with each other, thereby achieving good electrical contact. In particular, tin has excellent ionic conductivity, and carbon nanotubes have excellent electronic conductivity, so that the electrical properties of the half cell can be greatly improved.
[0079] 4 is an electrochemical cycle diagram of a half cell manufactured using the negative electrode material according to Example 1 of the present application. As can be seen from Fig. 4, the charge capacity of the half cell according to Example 1 at the first cycle is high at 2728 mAh / g, and the cycle capacity retention rate at the 100th cycle is 81.26%, indicating excellent electrochemical properties.
[0080] The above-described embodiments are only a part of the embodiments of the present application, but not all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the claimed application, but merely shows selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by a person skilled in the art without performing creative labor belong to the protection scope of the present application. [Industrial Applicability]
[0081] The negative electrode material according to the present application includes a silicon-based material, a carbon-coated tin nanowire, and a carbon nanotube. The carbon-coated tin nanowire and the carbon nanotube have a certain length and also have a certain flexibility and elasticity, and when mixed with a silicon-based material, they can form a three-dimensional conductive network structure, which can alleviate the volume effect of the negative electrode material caused by the intercalation and deintercalation of lithium, increase the specific capacity of the battery, and improve the cycle stability. In addition, the negative electrode material has high ionic conductivity and electronic conductivity, and improves the conductive ability. [Explanation of symbols]
[0082] 110 Silicon-based materials 120 Carbon-coated tin nanowires 130 Carbon Nanotubes
Claims
1. A negative electrode material comprising a silicon-based material, carbon-coated tin nanowires, and carbon nanotubes.
2. the silicon-based material includes at least one of silicon, a silicon alloy, and silicon monoxide; Or / and, the silicon element includes at least one of silicon nanoparticles, silicon nanosheets, and silicon nanowires, or / and, 2. The negative electrode material of claim 1, wherein the silicon alloy comprises at least one of an aluminum silicon alloy, a magnesium silicon alloy, a ferro-silicon alloy, and a silver silicon alloy.
3. The particle size of the silicon nanoparticles is 5 to 200 nm; Or / and the silicon nanosheet has a thickness of 5 to 100 nm and a planar size of 100 to 2000 nm, the negative electrode material according to claim 2 .
4. The negative electrode material according to claim 2, wherein the silicon nanowires have a diameter of 5 to 200 nm and a length of 50 to 2000 nm.
5. 4. The negative electrode material according to claim 1, wherein the surface of the silicon-based material is further covered with a carbon layer having a nanoscale thickness.
6. 6. The negative electrode material according to claim 5, wherein the carbon layer on the silicon-based material has a thickness of 2 to 10 nm.
7. The carbon-coated tin nanowires have a diameter of 100 nm or less and an aspect ratio of (5-1000):1; or / and the thickness of the carbon coating layer in the carbon-coated tin nanowires is nanoscale; or / and the degree of graphitization γ of the carbon coating layer in the carbon-coated tin nanowire satisfies 0.3≦γ≦1, where γ=(0.344−d 002 ) / (0.344-0.3354), where d 002 The negative electrode material according to any one of claims 1 to 3, characterized in that: is the layer spacing (unit: nm) on the 002 crystal plane of the carbon coating layer.
8. The negative electrode material according to claim 7, wherein the carbon coating layer on the carbon-coated tin nanowires has a thickness of 2 to 10 nm.
9. The carbon nanotubes have a diameter of 20 nm or less and an aspect ratio of (10 to 1000):1; Or / and the carbon nanotubes include at least single-walled carbon nanotubes.
10. 10. The negative electrode material of claim 9, wherein the carbon nanotubes are a mixture of single-walled carbon nanotubes and multi-walled carbon nanotubes.
11. The negative electrode material according to any one of claims 1 to 3, characterized in that the silicon content is 60% by weight to 98% by weight, the tin content is 0.5% by weight to 20% by weight, and the carbon content is 1.5% by weight to 20% by weight.
12. 4. The negative electrode material according to claim 1, further comprising carbon powder.
13. 13. The negative electrode material according to claim 12, wherein the carbon powder is one or more of graphite, hard carbon, and soft carbon.
14. A negative electrode sheet comprising the negative electrode material according to any one of claims 1 to 13.
15. mixing the anode material with a solvent, a conductive additive, and a binder to form an anode slurry; and applying the negative electrode slurry onto a negative electrode current collector and drying the negative electrode slurry to form the negative electrode sheet.
16. A lithium ion secondary battery comprising the negative electrode sheet according to claim 14.
17. combining the negative electrode sheet with a positive electrode sheet and a separator to form an electrode assembly; and placing the electrode group in a case and injecting an electrolyte to form the lithium ion secondary battery.
18. A lithium ion solid state battery comprising the negative electrode sheet according to claim 14.
19. 20. The method of claim 18, further comprising combining the negative electrode sheet with a positive electrode sheet and a solid electrolyte to form the lithium ion solid state battery.
Citation Information
Patent Citations
Flexible nano SnO2 / Si composite lithium ion battery negative-electrode material and preparation method thereof
CN103325998A
Negative electrode active substance, method of manufacturing same, negative electrode and lithium battery adopting same
JP2007115687A
Negative electrode for lithium ion secondary battery, lithium ion secondary battery using the same, slurry for negative electrode production for lithium ion secondary battery, and method of manufacturing negative electrode for lithium ion secondary battery
JP2010262754A
Composite coated nano-tin anode material and its manufacturing method and use
JP2021506056A
Negative active material for lithium secondary battery, method of preparing same, and lithium secondary battery comprising same
KR1020090109225A